Clinical relevance of the caroticoclinoid foramen - A case report and concise literature review - Andrzej Żytkowski; Janusz Skrzat; Agata Mazurek; Agata Majos; Maciej Radek; Tomasz Gładysz; Edward Clarke; Grzegorz Wysiadecki (Elsevier, 2021)
Aim: In this report, we described the case of bilateral caroticoclinoid foramen found on the isolated human sphenoid bone. Case description: Observed anatomical variant resulted from complete ossification of the caroticoclinoid ligament between the anterior and middle clinoid processes. The transverse diameter of the foramen on the right side was 6.7 mm, while on the left side, it was 6.31 mm. The foramen's vertical diameter on the right side was 6.33 mm, while on the left side, it was 6.17 mm. The length of the anterior clinoid process measured 11.43 mm on the right side and 11.55 mm on the left side. The distance between the base of the right and left middle clinoid process (i.e., at points where the ossified caroticoclinoid ligaments attached to the lateral borders of the sella turcica) was 10.32 mm. The length, anterior-posterior width, and thickness of the right ossified cariticoclinoid ligament were 6.75 mm, 3.41 mm, and 1.21 mm accordingly. The same parameters measured for the left ossified cariticoclinoid ligament were 6.28 mm, 2.89 mm, and 1.58 mm. Conclusions: The presence of caroticoclinoid foramen may impact the internal carotid artery passing through the sphenoid bone and thus interfere with the success of surgical procedures performed in the sellar region.